Easily dispersible nano silicon dioxide and preparation method of rubber composite material thereof

By introducing active sites and bonding modifiers to the surface of silica through a mechanical-chemical modification method, the problem of easy agglomeration of nano-silica in composite materials was solved, and its good dispersion and performance improvement in polymer matrix were achieved.

CN120865620APending Publication Date: 2025-10-31FOSHAN JINYANSHENG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510800763.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Nano-silica is prone to agglomeration in composite materials, which prevents it from fully realizing its properties. Existing modification methods are difficult to effectively solve the dispersion problem of nano-silica in polymer matrices.

Method used

A mechanical-chemical modification method was adopted to introduce active sites on the surface of silica using a high-energy sand mill, which were then bonded to a modifier to form a steric hindrance effect, thereby limiting agglomeration and preparing easily dispersible nano silica powder.

Benefits of technology

The prepared nano-silica powder is well dispersed in the polymer matrix, which enhances the mechanical properties of the material. It is also safe, environmentally friendly, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

According to the easily-dispersed nano silicon dioxide powder and the application of the rubber composite material of the easily-dispersed nano silicon dioxide powder, safe, non-toxic and cheap raw materials are used for carrying out surface modification on nano silicon dioxide synthesized by a hydration precipitation method, the nano silicon dioxide powder with excellent dispersing performance and large specific surface area is prepared, and the rubber composite material is prepared by compounding the nano silicon dioxide powder with rubber. According to the present invention, the modified nano-silica can be well dispersed in the rubber matrix, and the tensile strength test results show that the modified nano-silica can substantially improve the tensile strength of the rubber composite material, and the tensile strength can achieve 794 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanomaterials, and in particular to a method for preparing easily dispersible nano-silica and its rubber composite material. Background Technology

[0002] Silica, abundant in the Earth's crust and simple to synthesize industrially, has long been considered one of the best inorganic fillers in composite materials, and has become the most widely used inorganic material in industry. However, due to the abundance of active groups such as hydroxyl groups in silica, serious particle aggregation problems occur in composite materials during industrial applications, leading to severe agglomeration and preventing the material from exhibiting its excellent performance. Therefore, the modification and preparation of easily dispersible nano-silica has become a focus of many researchers.

[0003] Modification of nano-silica mainly includes surface modification. By using dispersants and simple grinding processes, nano-silica slurries with relatively small particle sizes can be obtained. However, during the drying process, nano-silica particles will exhibit severe agglomeration, making them unsuitable for use in many solid materials. Therefore, the research on easily dispersible nano-silica powder is destined to become the next research hotspot.

[0004] This invention mainly utilizes mechanical-chemical modification to generate active sites on the surface of silica through the grinding efficiency of a high-energy sand mill. Simultaneously, the hydroxyl active groups on the surface of nano-silica can bond with the modifier more quickly, thus effectively overcoming the influence of surface hydrogen bonds. At the same time, the modifier can form spatial positions on the surface of nano-silica particles, effectively limiting the agglomeration of nano-silica, and successfully preparing an easily dispersible nano-silica powder. Summary of the Invention

[0005] Based on this, the present invention provides a nano-silica powder with good dispersibility, is not prone to agglomeration, can be well dispersed in a polymer matrix, enhances the mechanical properties of polymers, and is safe, environmentally friendly, and can be industrially produced.

[0006] The present invention is achieved through the following technical solution.

[0007] A type of easily dispersible nano-silica powder, modified by a process comprising 1 part nano-silica and 1-5 parts of ethanol as a dispersion medium.

[0008] The easily dispersible nano-silica is a surface-modified nano-silica powder;

[0009] The nano-silica modifier includes one or more of the following: KH570, polyethylene glycol 400, and polyvinylpyrrolidone (K30).

[0010] In one embodiment, the mass ratio of the modifier to the nano-silica is (0.01 to 0.1):1.

[0011] In one embodiment, the preparation of the easily dispersible nano-silica includes the following steps: mixing nano-silica, a dispersant, and a dispersion medium of ethanol, ultrasonicating for 10-20 min, and stirring; wherein the stirring conditions include: a rotation speed of 100 r / min-800 r / min and a duration of 15 min-30 min; then adding the stirred nano-silica slurry to a sand mill for grinding at a rotation speed of 1600 r / min-2800 r / min for 2-4 h, followed by washing, filtering, and drying.

[0012] In one embodiment, the mass ratio of the nano-silica to the dispersion medium ethanol is 1:(1-5).

[0013] In one embodiment, the mass ratio of the nano-silica to the dispersant is 1:(0.01 to 0.1).

[0014] The present invention also provides an application of the nano silica gel described above in rubber composite materials.

[0015] The present invention also provides a rubber composite material, wherein the components of the rubber composite material include 45 parts of butadiene rubber (BR900), 25 parts of natural rubber, 20 parts of easily dispersible nano silica, 5 parts of zinc oxide, 2 parts of stearic acid, 2.5 parts of additives, 0.06 parts of vulcanizing agent, 0.02 parts of vulcanizing auxiliaries, and 0.02 parts of anti-vulcanizing agent.

[0016] The present invention also provides a method for preparing the rubber composite material as described above, comprising the following steps:

[0017] The components of the rubber composite material were mixed and stirred in an internal mixer at a temperature of 160°C for 15 minutes. Then, the mixture was transferred to an open mill. The first stage was carried out at 50°C for 5 minutes, the second stage at 80°C for 3 minutes, and the third stage at 150°C for 30 minutes. The mixed rubber composite was then transferred to a flat vulcanizing apparatus. The vulcanization conditions were as follows: first stage at 100°C for 3 minutes, second stage at 150°C for 5 minutes, third stage at 165°C for 5 minutes, 170°C for 5 minutes, fourth stage at 175°C for 5 minutes, and fifth stage at 175°C for 10 minutes.

[0018] In one embodiment, the open-milling process is carried out at room temperature in a natural environment.

[0019] Compared with the prior art, the nano-silica of the present invention has the following superior effects:

[0020] The modified nano-silica powder of this invention has a large specific surface area, low oil absorption value, and no obvious agglomeration phenomenon after being compounded with rubber. The mechanical properties are good as tested by a universal tensile testing machine.

[0021] Furthermore, the raw materials required for the nano-silica powder of the present invention are non-toxic, inexpensive, and safe, and the preparation process is suitable for industrial-scale production. Detailed Implementation

[0022] To facilitate understanding of the present invention, a more comprehensive description will be provided below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.

[0023] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of the invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified. In the description of the present invention, "a number" means at least one, such as one, two, etc., unless otherwise explicitly specified.

[0024] The terms "preferred," "more preferably," etc., used in this invention refer to embodiments of the invention that provide certain beneficial effects under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this invention.

[0025] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0027] This invention provides a method for preparing easily dispersible nano-silica powder, which, by weight, comprises 1 part nano-silica, 1 to 5 parts ethanol, and (0.01 to 0.1) modifier.

[0028] The modifier is made from safe, inexpensive, and non-toxic raw materials. It can be used as a modifier, dispersant, and interfacial adhesive on the surface of nano-silica powder particles. The resulting nano-silica powder has the advantages of good stability, large specific surface area, non-agglomeration, and good interfacial adhesion to rubber matrix.

[0029] In a specific example, the nano-silica is commercially available nano-silica synthesized by hydration precipitation.

[0030] In a specific example, the particle size of nano-silica ranges from 200 nm to 4000 nm.

[0031] Understandably, in this invention, the particle size of nano-silica includes, but is not limited to, 200nm, 400nm, 600nm, 800nm, 1000nm, 2000nm, 3000nm, and 4000nm.

[0032] In a preferred example, the purity of the nano-silica is 99.6%.

[0033] In a preferred example, all modifiers are commercially available, and the dispersion medium, ethanol, is commercially available analytical grade.

[0034] In a specific example, the mass ratio of the modifier to nano-silica is (0.01 to 0.1):1.

[0035] Understandably, in this invention, the mass ratio of dispersant to nano-silica includes, but is not limited to, 0.01:1, 0.03:1, 0.05:1, 0.07:1, 0.09:1, and 0.1:1.

[0036] The inventors improved the dispersibility of nano-silica in ethanol by grafting one or more of the modifiers selected in the invention onto nano-silica. The prepared nano-silica powder has a large specific surface area, low oil absorption value, and good interfacial adhesion to the rubber matrix.

[0037] In one specific example, the nano-silica has a purity of 99.6% and is in powder form.

[0038] More specifically, the particle size of silica is 200 nm to 4000 nm. It can be understood that, in this invention, the particle size of nano-silica includes, but is not limited to, 200 nm, 400 nm, 600 nm, 800 nm, 1000 nm, 2000 nm, 3000 nm, and 4000 nm.

[0039] In a specific example, the dispersion medium is ethanol (analytical grade), and the modifier is a commercially available product.

[0040] In a specific example, the mass ratio of the modifier to nano-silica is (0.01 to 0.1):1.

[0041] Understandably, in this invention, the mass ratio of dispersant to nano-silica includes, but is not limited to, 0.01:1, 0.03:1, 0.05:1, 0.07:1, 0.09:1, and 0.1:1. Preferably, the mass ratio of dispersant to nano-silica is (0.06 to 0.1):1.

[0042] In a specific example, the preparation of easily dispersible nano-silica powder includes the following steps: mixing nano-silica, dispersant and dispersion medium ethanol, sonicating for 10-20 min, and stirring; wherein the stirring conditions include: rotation speed of 100 r / min-800 r / min; duration of 20 min-40 min; then adding the stirred nano-silica slurry into a sand mill for grinding, with a grinding speed of 1600 r / min-2800 r / min and a grinding time of 2-4 h, followed by washing, filtering and drying.

[0043] Understandably, in this invention, the stirring speed includes, but is not limited to, 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, and 800 r / min. Preferably, the stirring speed is 600-800 r / min.

[0044] Understandably, the stirring time in this invention includes, but is not limited to, 20 min, 25 min, 30 min, 35 min, and 40 min. Preferably, the stirring time is 20 min to 40 min.

[0045] In one specific example, the grinding media used is zirconia beads.

[0046] In one specific example, the zirconium oxide beads used for grinding have a particle size of 0.1 mm to 0.3 mm. It is understood that in this invention, the particle size of the zirconium oxide beads used for grinding includes, but is not limited to, 0.1 mm, 0.2 mm, and 0.3 mm. Preferably, the particle size of the zirconium oxide beads used for grinding is 0.1 mm to 0.2 mm.

[0047] In a specific example, the sand mill is a vertical sand mill. After the sand milling is completed, the nano-silica slurry is filtered out, and then cleaned by ultrasonication, filtered, and dried.

[0048] In a specific example, the mass ratio of nano-silica to the dispersion medium ethanol is 1:(1-5).

[0049] Understandably, in this invention, the mass ratio of nano-silica to the dispersion medium ethanol includes, but is not limited to, 1:1, 1:2, 1:3, 1:4, and 1:5.

[0050] In a specific example, the mass ratio of the grinding media, zirconia beads, to nano-silica is (2-15):1.

[0051] Understandably, in this invention, the mass ratio of the abrasive media, zirconium oxide beads, to nano-silica includes, but is not limited to, 2:1, 4:1, 6:1, 8:1, 10:1, 12:1, 14:1, and 15:1.

[0052] In one specific example, the dispersion medium is ethanol, commercially available analytical grade.

[0053] In one specific example, the stirring temperature is 20℃-40℃. It is understood that in this invention, the stirring temperature includes, but is not limited to, 20℃, 30℃, and 40℃.

[0054] In one specific example, the sanding is carried out in a natural environment.

[0055] In a preferred example, a vertical sand mill is selected. The modifier is bonded to the active hydroxyl groups on the surface of nano-silica through high-energy sand milling. Simultaneously, the high-energy milling process creates "active sites" on the silica surface, grafting the modifier onto the nano-silica particles and forming a steric hindrance effect. This effectively limits the formation of hard agglomerates due to the large specific surface area and high surface energy of the nano-silica particles as their size decreases. During the drying process, this effectively overcomes the agglomeration problem of nano-silica, resulting in nano-silica powder with a large specific surface area.

[0056] The present invention also provides an application of the easily dispersible nano silica powder as described above in a rubber composite material.

[0057] The present invention also provides a method for preparing a rubber composite material, wherein the rubber composite material comprises 45 parts of butadiene rubber (BR900), 25 parts of natural rubber, 20 parts of easily dispersible nano silica, 5 parts of zinc oxide, 2 parts of stearic acid, 2.5 parts of additives, 0.06 parts of vulcanizing agent, 0.02 parts of vulcanizing auxiliaries, and 0.02 parts of anti-vulcanizing agent.

[0058] The present invention also provides a method for preparing the above-mentioned rubber composite material, comprising the following steps:

[0059] The components of the rubber composite material were mixed and stirred in an internal mixer at a temperature of 160°C for 15 minutes. Then, the mixture was transferred to an open mill. The first stage was carried out at 50°C for 5 minutes, the second stage at 80°C for 3 minutes, and the third stage at 150°C for 30 minutes. The mixed rubber composite was then transferred to a flat vulcanizing apparatus. The vulcanization conditions were as follows: first stage at 100°C for 3 minutes, second stage at 150°C for 5 minutes, third stage at 165°C for 5 minutes, 170°C for 5 minutes, fourth stage at 175°C for 5 minutes, and fifth stage at 175°C for 10 minutes.

[0060] In a specific example, the stirring temperature is 20℃~40℃.

[0061] In a specific example, the stirring speed is 100-800 r / min.

[0062] In a specific example, after the rubber is vulcanized, it is necessary to cut the sample, test the sample thickness and width, and then test the mechanical properties of the rubber sample.

[0063] The following detailed description, with reference to specific embodiments, illustrates the preparation method of easily dispersible nano-silica and its application in rubber composites according to the present invention. Unless otherwise specified, all raw materials used in the following embodiments are commercially available products.

[0064] Example 1

[0065] This embodiment provides a method for preparing easily dispersible nano-silica and its application in rubber composites, as detailed below:

[0066] Step 1: Preparation of easily dispersible nano-silica powder

[0067] Weigh 450g of commercially available nano-silica, 1.5kg of ethanol, 5g of modifier KH570, 2ml of glacial acetic acid, and 5ml of deionized water into a 3L beaker. Sonicate for 15min and mechanically stir for 20min. Then add the stirred slurry to the material tank of a sand mill. Start at a speed of 1800r / min and grind for 30min. Increase the speed to 2800r / min and grind for 3h. Discharge the material and filter to remove the solvent. Add 1kg of ethanol, stir and wash, and filter again. Repeat this process 3-4 times. Dry in an oven at 150℃ for 24h.

[0068] Step 2: Preparation of rubber composite material

[0069] The rubber composite material is prepared by weight, and the components of the rubber composite material include 45 parts of butadiene rubber (BR900), 25 parts of natural rubber, 20 parts of easily dispersible nano silica, 5 parts of zinc oxide, 2 parts of stearic acid, 2.5 parts of additives, 0.06 parts of vulcanizing agent, 0.02 parts of vulcanizing auxiliaries, and 0.02 parts of anti-vulcanizing agent.

[0070] The components of the rubber composite material were mixed and stirred in an internal mixer at a temperature of 160℃ for 15 minutes. Then, the mixture was transferred to an open mill. The first stage was carried out at 50℃ for 5 minutes, the second stage at 80℃ for 3 minutes, and the third stage at 150℃ for 30 minutes. The mixed rubber composite was then transferred to a flat vulcanizing apparatus. The vulcanization conditions were as follows: first stage at 100℃ for 3 minutes, second stage at 150℃ for 5 minutes, third stage at 165℃ for 5 minutes, 170℃ for 5 minutes, fourth stage at 175℃ for 5 minutes, and fifth stage at 175℃ for 10 minutes.

[0071] Example 2

[0072] This embodiment provides a method for preparing easily dispersible nano-silica and its application in rubber composites, as detailed below:

[0073] Step 1: Preparation of easily dispersible nano-silica powder

[0074] Weigh 300g of commercially available nano-silica, 1.5kg of ethanol, and 15g of polyethylene glycol 400 modifier, add them to a 3L beaker, sonicate for 15min, mechanically stir for 20min, then add the stirred slurry to the material tank of a sand mill, start at 1800r / min, grind for 30min, then increase the speed to 2800r / min and grind for 4h, discharge the material, then filter the ground slurry to remove the solvent, add 1kg of ethanol, stir and wash, filter again, repeat 3-4 times, and then dry in an oven at 150℃ for 24h.

[0075] Step 2: Preparation of rubber composite material

[0076] The rubber composite material is prepared by weight, and the components of the rubber composite material include 45 parts of butadiene rubber (BR900), 25 parts of natural rubber, 20 parts of easily dispersible nano silica, 5 parts of zinc oxide, 2 parts of stearic acid, 2.5 parts of additives, 0.06 parts of vulcanizing agent, 0.02 parts of vulcanizing auxiliaries, and 0.02 parts of anti-vulcanizing agent.

[0077] The components of the rubber composite material were mixed and stirred in an internal mixer at a temperature of 160℃ for 15 minutes. Then, the mixture was transferred to an open mill. The first stage was carried out at 50℃ for 5 minutes, the second stage at 80℃ for 3 minutes, and the third stage at 150℃ for 30 minutes. The mixed rubber composite was then transferred to a flat vulcanizing apparatus. The vulcanization conditions were as follows: first stage at 100℃ for 3 minutes, second stage at 150℃ for 5 minutes, third stage at 165℃ for 5 minutes, 170℃ for 5 minutes, fourth stage at 175℃ for 5 minutes, and fifth stage at 175℃ for 10 minutes.

[0078] Example 3

[0079] This embodiment provides a method for preparing easily dispersible nano-silica and its application in rubber composites, as detailed below:

[0080] Step 1: Preparation of easily dispersible nano-silica powder

[0081] Weigh 1 kg of commercially available nano-silica, 1.5 kg of ethanol, and 10 g of modifier polyvinylpyrrolidone (K30) into a 3 L beaker. Sonicate for 15 min and mechanically stir for 20 min. Then add the stirred slurry into the material tank of a sand mill. Start at a speed of 1800 r / min and grind for 30 min. Increase the speed to 2900 r / min and grind for 2 h. Discharge the material and filter the slurry to remove the solvent. Add 1 kg of ethanol, stir and wash, and filter again. Repeat this process 3-4 times. Then dry in an oven at 150℃ for 24 h.

[0082] Step 2: Preparation of rubber composite material

[0083] The rubber composite material is prepared by weight, and the components of the rubber composite material include 45 parts of butadiene rubber (BR900), 25 parts of natural rubber, 20 parts of easily dispersible nano silica, 5 parts of zinc oxide, 2 parts of stearic acid, 2.5 parts of additives, 0.06 parts of vulcanizing agent, 0.02 parts of vulcanizing auxiliaries, and 0.02 parts of anti-vulcanizing agent.

[0084] The components of the rubber composite material were mixed and stirred in an internal mixer at a temperature of 160℃ for 15 minutes. Then, the mixture was transferred to an open mill. The first stage was carried out at 50℃ for 5 minutes, the second stage at 80℃ for 3 minutes, and the third stage at 150℃ for 30 minutes. The mixed rubber composite was then transferred to a flat vulcanizing apparatus. The vulcanization conditions were as follows: first stage at 100℃ for 3 minutes, second stage at 150℃ for 5 minutes, third stage at 165℃ for 5 minutes, 170℃ for 5 minutes, fourth stage at 175℃ for 5 minutes, and fifth stage at 175℃ for 10 minutes.

[0085] Example 4

[0086] This embodiment provides a method for preparing easily dispersible nano-silica and its application in rubber composites, as detailed below:

[0087] Step 1: Preparation of easily dispersible nano-silica powder

[0088] Weigh 300g of commercially available nano-silica, 1.5kg of ethanol, 5g of polyethylene glycol 400 modifier, and 10g of polyvinylpyrrolidone (K30) into a 3L beaker. Sonicate for 15min and mechanically stir for 20min. Then add the stirred slurry to the material tank of a sand mill. Start at a speed of 1800r / min and grind for 30min. Increase the speed to 2900r / min and grind for 1h. Then add the prepared KH-570 solution (KH-570: 5g, glacial acetic acid 2ml, deionized water 5ml, ethanol 20g) and grind for another 3h. Discharge the material and filter the slurry to remove the solvent. Add 1kg of ethanol, stir and wash, and filter again. Repeat this process 3-4 times. Then dry in an oven at 150℃ for 24h.

[0089] Step 2: Preparation of rubber composite material

[0090] The rubber composite material is prepared by weight, and the components of the rubber composite material include 45 parts of butadiene rubber (BR900), 25 parts of natural rubber, 20 parts of easily dispersible nano silica, 5 parts of zinc oxide, 2 parts of stearic acid, 2.5 parts of additives, 0.06 parts of vulcanizing agent, 0.02 parts of vulcanizing auxiliaries, and 0.02 parts of anti-vulcanizing agent.

[0091] The components of the rubber composite material were mixed and stirred in an internal mixer at a temperature of 160℃ for 15 minutes. Then, the mixture was transferred to an open mill. The first stage was carried out at 50℃ for 5 minutes, the second stage at 80℃ for 3 minutes, and the third stage at 150℃ for 30 minutes. The mixed rubber composite was then transferred to a flat vulcanizing apparatus. The vulcanization conditions were as follows: first stage at 100℃ for 3 minutes, second stage at 150℃ for 5 minutes, third stage at 165℃ for 5 minutes, 170℃ for 5 minutes, fourth stage at 175℃ for 5 minutes, and fifth stage at 175℃ for 10 minutes.

[0092] Comparative Example 1

[0093] This comparative example provides a method for preparing easily dispersible nano-silica and its application in rubber composites, as detailed below:

[0094] Step 1: Preparation of nano-silica powder

[0095] Weigh 300g of commercially available nano-silica, 1.5kg of ethanol, 5g of polyethylene glycol 400 modifier, and 10g of polyvinylpyrrolidone (K30) into a 3L beaker. Sonicate for 15min, mechanically stir for 1h, then add the prepared KH-570 solution (KH-570: 5g, glacial acetic acid 2ml, deionized water 5ml, ethanol 20g), stir for another 4h, discharge the material, and then filter the ground slurry to remove the solvent. Add 1kg of ethanol, stir and wash, filter again, repeat 3-4 times, and then dry in an oven at 150℃ for 24h.

[0096] Step 2: Preparation of rubber composite material

[0097] The rubber composite material is prepared by weight, and the components of the rubber composite material include 45 parts of butadiene rubber (BR900), 25 parts of natural rubber, 20 parts of easily dispersible nano silica, 5 parts of zinc oxide, 2 parts of stearic acid, 2.5 parts of additives, 0.06 parts of vulcanizing agent, 0.02 parts of vulcanizing auxiliaries, and 0.02 parts of anti-vulcanizing agent.

[0098] The components of the rubber composite material were mixed and stirred in an internal mixer at a temperature of 160℃ for 15 minutes. Then, the mixture was transferred to an open mill. The first stage was carried out at 50℃ for 5 minutes, the second stage at 80℃ for 3 minutes, and the third stage at 150℃ for 30 minutes. The mixed rubber composite was then transferred to a flat vulcanizing apparatus. The vulcanization conditions were as follows: first stage at 100℃ for 3 minutes, second stage at 150℃ for 5 minutes, third stage at 165℃ for 5 minutes, 170℃ for 5 minutes, fourth stage at 175℃ for 5 minutes, and fifth stage at 175℃ for 10 minutes.

[0099] Comparative Example 2

[0100] This embodiment provides a method for preparing easily dispersible nano-silica and its application in rubber composites, as detailed below:

[0101] Step 1: Nano-silica powder

[0102] Commercially available nano-silica powder was used in the experiment.

[0103] Step 2: Preparation of rubber composite material

[0104] The rubber composite material is prepared by weight, and the components of the rubber composite material include 45 parts of butadiene rubber (BR900), 25 parts of natural rubber, 20 parts of commercially available nano silica, 5 parts of zinc oxide, 2 parts of stearic acid, 2.5 parts of additives, 0.06 parts of vulcanizing agent, 0.02 parts of vulcanizing auxiliaries, and 0.02 parts of anti-vulcanizing agent.

[0105] The components of the rubber composite material were mixed and stirred in an internal mixer at a temperature of 160℃ for 15 minutes. Then, the mixture was transferred to an open mill. The first stage was carried out at 50℃ for 5 minutes, the second stage at 80℃ for 3 minutes, and the third stage at 150℃ for 30 minutes. The mixed rubber composite was then transferred to a flat vulcanizing apparatus. The vulcanization conditions were as follows: first stage at 100℃ for 3 minutes, second stage at 150℃ for 5 minutes, third stage at 165℃ for 5 minutes, 170℃ for 5 minutes, fourth stage at 175℃ for 5 minutes, and fifth stage at 175℃ for 10 minutes.

[0106] Preparation of easily dispersible nano-silica powder obtained in Examples 1-4 and Comparative Examples 1 and 2, and verification of its effect in rubber composite materials.

[0107] As shown in Table 1, after modification, the nano-silica powder showed little change in purity, pH, ignition alkalinity, and specific gravity. The main changes were in oil absorption value and specific surface area. After modification, the oil absorption value decreased from 2.43 g / 100 g to 1.21 g / 100 g, indicating that the modified nano-silica possesses excellent hydrophobic properties. This also demonstrates that the hydroxyl groups on the silica surface were bonded by the modifier, making the surface hydrophobic. The specific surface area increased from the initial 186 m² / g. 2 / g increased to 231m 2 / g indicates that the particle size of nano-silica was effectively reduced during the modification process, and no obvious agglomeration occurred during the drying process, indicating that the nano-silica powder has a good dispersion effect.

[0108] Table 1. Test results of silica powder in the examples and comparative examples

[0109] Sample Name pH purity Loss on ignition proportion Oil absorption value Specific surface area Example 1 6.98 96.8 6.54% 0.2759 1.31 <![CDATA[196m 2 / g]]> Example 2 6.97 96.5 6.60% 0.2761 1.29 <![CDATA[205m 2 / g]]> Example 3 6.94 96.6 6.64% 0.2763 1.28 <![CDATA[213m 2 / g <!-- 7 -->]]> Example 4 6.89 96.2 6.68% 0.2764 1.21 <![CDATA[231m 2 / g]]> Comparative Example 1 6.98 96.7 6.82% 0.2768 1.29 <![CDATA[192m 2 / g]]> Comparative Example 2 6.92 96.4 6.51% 0.2756 2.43 <![CDATA[186m 2 / g]]>

[0110] Table 2. Tensile property testing of rubber composites

[0111] Sample Name Width (mm) Thickness(mm) Elongation at break Tensile strength Example 1 10.24 0.45 889.336 621 Example 2 10.31 0.45 813.445 689 Example 3 9.86 0.45 598.662 752 Example 4 9.54 0.45 569.967 794 Comparative Example 1 10.52 0.48 965.681 612 Comparative Example 2 11.35 0.63 1027.28 453

[0112] As shown in Table 2, Comparative Example 2, which only added 20 parts of ordinary nano-silica to the rubber composite material, had a tensile strength of 453 MPa. This indicates that the ordinary nano-silica had poor interfacial adhesion to the rubber composite material, and the nano-silica could not be well dispersed in the rubber's spatial network structure, resulting in severe agglomeration and low tensile strength. In contrast, the modified nano-silica, due to its large specific surface area, good particle dispersion, and good interfacial adhesion to the rubber, could be well dispersed in the rubber matrix, thus greatly improving the mechanical properties of the rubber composite material. From the tensile strength analysis, the nano-silica prepared in Example 4, after adding 20%, achieved a tensile strength of 794 MPa, indicating that the modified nano-silica was easily dispersed in the rubber matrix and could effectively improve the mechanical properties of the rubber composite material.

[0113] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0114] The embodiments described above are merely illustrative of several implementations of the present invention, facilitating a detailed understanding of the technical solutions of the present invention, but should not be construed as limiting the scope of protection of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention. It should be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided by the present invention through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this invention patent should be determined by the content of the appended claims, and the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing easily dispersible nano-silica powder, characterized in that, The prepared powder has a specific surface area of ​​231 m². 2 / g, oil absorption value 1.21g / 100g; The modified nano-silica is commercially available nano-silica synthesized by hydration precipitation method; The easily dispersible nano silica modification includes nano silica, a dispersion medium of ethanol, and a modifier.

2. The easily dispersible nano-silica modification according to claim 1, characterized in that, The mass ratio of the nano-silica to the ethanol is 1:(1-5).

3. The easily dispersible nano-silica according to claim 1, characterized in that, The mass ratio of the dispersant to the nano-silica is (0.01-0.1):

1.

4. The easily dispersible nano-silica according to claim 1, characterized in that, The preparation of the nano-silica includes the following steps: mixing nano-silica, dispersant and dispersion medium, ultrasonicating and stirring; wherein, ultrasonication for 10-30 min, and stirring conditions include: rotation speed of 100 r / min-800 r / min; duration of 20 min-40 min; then adding the stirred nano-silica slurry into a sand mill for grinding, with a grinding speed of 1500 r / min-3000 r / min and a grinding time of 2-4 h.

5. The easily dispersible nano-silica according to claim 4, characterized in that, The mass ratio of the nano-silica to the dispersion medium ethanol is 1:(1-5); and the mass ratio of the nano-silica to the dispersant is 1:(0.01-0.1).

6. The easily dispersible nano-silica according to claim 4, characterized in that, The dispersion medium is ethanol.

7. The application of the easily dispersible nano-silica according to any one of claims 1 to 6 in rubber composite materials.

8. The rubber composite material according to claim 7, characterized in that, By weight, the components of the rubber composite material include 45 parts of butadiene rubber (BR900), 25 parts of natural rubber, 20 parts of easily dispersible nano silica, 5 parts of zinc oxide, 2 parts of stearic acid, 2.5 parts of additives, 0.06 parts of vulcanizing agent, 0.02 parts of vulcanizing auxiliaries, and 0.02 parts of anti-vulcanizing agent.

9. A method for preparing a rubber composite material according to claim 8, characterized in that, Includes the following steps: The components of the rubber composite material are mixed and stirred by internal mixing at a temperature of 160°C for 15 minutes. Then, the mixture is transferred to an open mill. The first stage is at 50°C for 5 minutes, the second stage is at 80°C for 3 minutes, and the third stage is at 150°C for 30 minutes. The mixed rubber composite is then transferred to a flat vulcanizing apparatus. The vulcanization conditions are as follows: first stage 100°C for 3 minutes, second stage 150°C for 5 minutes, third stage 165°C for 5 minutes, 170°C for 5 minutes, fourth stage 175°C for 5 minutes, and fifth stage 175°C for 10 minutes.

10. The method for preparing the rubber composite material according to claim 9, characterized in that, The refining process was carried out at room temperature.